From The Laboratory Of The 1990s To The Novel Of The 21st Century – Contemporary Bulgarian Literature In Highlights - Dimitrova, Elka (Slavica Lodziensia, 2017)
The text presents the main trends in Bulgarian literary development from the 1990s to the present day through the highlights of the lyrical boom of the 1990s and the novel wave since 2001 on. Some lines of continuity are outlined, tracing back to the 1960s (regarding the literary experiment and dissident attitude), and the period before 1944 (the adoption/challenge of the modernist tradition in the 1990s). A separate research topic is the fi xation of the critical interest on certain writers’ personalities.